A cis Repression Sequence Adjacent to the Transcription Start Site of the Human Cytomegalovirus US3 Gene Is Required To Down Regulate Gene Expression at Early and Late Times after Infection - Lashmit, Philip E. (American Society for Microbiology, 1998)
Human cytomegalovirus has two enhancer-containing immediate-early (IE) promoters with a cis repression sequence (CRS) positioned immediately upstream of the transcription start site, designated the major IE (MIE) promoter and the US3 promoter. The role of the CRS upstream of the US3 transcription start site in the context of the viral genome was determined by comparing the levels of transcription from these two enhancer-containing promoters in recombinant viruses with a wild-type or mutant CRS. Upstream of the CRS of the US3 promoter was either the endogenous enhancer (R(2)) or silencer (R(1)). The downstream US3 gene was replaced with the indicator gene chloramphenicol acetyltransferase (CAT). Infected permissive human fibroblast cells or nonpermissive, undifferentiated monocytic THP-1 cells were analyzed for expression from the US3 promoter containing either the wild-type or mutant CRS. With the wild-type CRS, the maximum level of transcription in permissive cells was detected within 4 to 6 h after infection and then declined. With the mutant CRS and the R(2) enhancer upstream, expression from the US3 promoter continued to increase throughout the viral replication cycle to levels 20- to 40-fold higher than for the wild type. In nonpermissive or permissive monocytic THP-1 cells, expression from the US3 promoter was also significantly higher when the CRS was mutated. Less expression was obtained when only the R(1) element was present, but expression was higher when the CRS was mutated. Thus, the CRS in the enhancer-containing US3 promoter appears to allow for a short burst of US3 gene expression followed by repression at early and late times after infection. Overexpression of US3 may be detrimental to viral replication, and its level of expression must be stringently controlled. The role of the CRS and the viral IE86 protein in controlling enhancer-containing promoters is discussed.